Causes and consequences of variation in blue tit nest construction - Järvinen, Pauliina (fi=Turun yliopisto|en=University of Turku|, 2020)
Species across taxa and the vast majority of birds build nests for reproduction. The bird nest functions as a receptacle for the eggs and young and as such determines successful reproduction. Through nest construction birds are able to extend control over the environment and to create a suitable microclimate for incubation and nestling development. Nests of the order Passeriformes are the most varied out of any group of birds. Intriguingly, variation in size and components can be observed both between and within species nest design. In the present thesis, I investigated the causes and consequences of the variation in nest size and components in a population of blue tits, Cyanistes caeruleus, in Southern Finland. In chapter I, I studied the effects of an experimental manipulation of nest size (height of the nest material within the nest box) on different breeding parameters related to nestling growth and female somatic condition. Variation in nest size is hypothesised to relate to varying requirements for insulation due to differences in latitude or ambient temperature. In line with the hypothesis, I expected the increased insulatory capacity of the experimentally enlarged nests to be reflected in nestling development and/ or in improved female somatic condition due to a reduced requirement for nest attendance. Blue tit chicks are ectothermic until they reach 7-8 days of age and rely mainly on the female’s body heat until then to maintain their body temperature. I found little support for the thermoregulation hypothesis as only the nestling tail length increased significantly in experimentally enlarged nests. Other studies have found that instead of an increase in nest height, which is mostly contributed to by the base layer of moss and grass, more important to insulation are the mass and material components of the nest cup lining. In chapters II-IV, my objective was to determine the evolutionary potential of variation in nest construction. In chapter II, I regarded the nest size and material components as potential invididual traits, whereby I studied the between-individual consistency (repeatability) and heritability in these nest characteristics by means of quantitative genetics. Because repeatability sets the upper limit for heritability, it provides a reasonable stepping-stone for further analysis of heritability. I found that both nest size and the proportion of feathers were repeatable female traits, and by further analysis, discovered that the latter was also a modestly heritable (albeit not statistically significant) trait limited to females in blue tits. In chapter III, I studied nest ornamentation in blue tits and the behavioural correlations between the different nest traits. Nest ornaments are conspicuous material placed on top of the nest, typically feathers (which I focused on here), but can also be flower petals, human-made material, colourful plastics or other unusual material. I found that nest ornamentation was a repeatable behaviour in female blue tits, which contradicts with other studies conducted in a different population of blue tits, in which feather ornaments were provided by males, not females. I also found that nest ornamentation and the proportion of feathers in the nest formed an extended phenotype syndrome, a term which was introduced here. Instead of using direct observations of individual behaviour, which are required in studying behavioural syndromes, I studied the behaviours by proxy, using measurements of nests as physical remnants of nest construction behaviour. A syndrome in nest building implies that blue tits are restricted in flexibility in their response to change in their nesting environment. In chapter IV, I studied selection in blue tit nest construction. I investigated whether nest characteristics have consequences on female fitness by studying her reproductive success in terms of nestling survival and offspring recruitment. I found that although nest characteristics were not related to nestling survival, the propensity to use feathers in the nest significantly increased recruitment probability. This is a significant finding and in combination with our other results (II) provides first evidence of selection in avian nest construction. Experimental studies are warranted to determine the selective advantage provided by the nest feather content, for it appears to become beneficial only after the offspring have left the nest. In this thesis, I investigated some of the causes and consequences of variation in blue tit nest construction. By means of an experimental set-up, I discovered that the height of the nest material is likely to have only a negligible effect on nest thermoregulation (I). I found that nest ornamentation, nest height and the proportion of feathers in the nest are repeatable female traits (II, III), and provided first pedigree-wide quantitative genetic evidence of heritability in avian nest construction (II). Moreover, I discovered that the modestly heritable trait in female blue tits has consequences for female fitness and is thus subject to selection (IV). However, my finding that the proportion of feathers forms an extended phenotype syndrome with nest ornamentation implies a limitation in the range of adaptive response to environmental change (IV).

Sinitiaisten pesänrakennuskäyttäytymisen vaihtelun syyt ja seuraukset Useat eläinlajit ja miltei kaikki linnut rakentavat pesiä lisääntymiseen. Linnunpesä suojaa munia ja poikasia sääolosuhteilta sekä ympäristön uhilta ja määrittää näin lisääntymismenestystä. Rakentamalla pesän linnut luovat sopivat olosuhteet haudonnalle ja jälkeläisten kehitykselle. Pesien koot ja kompositiot vaihtelevat niin lajiensisäisesti kuin lajien välillä. Varpuslintujen (Passeriformes) pesissä on kaikista lintulahkoista eniten vaihtelua. Väitöskirjassani tutkin sinitiaisten (Cyanistes caeruleus) pesien koko- ja materiaalivaihtelun syitä ja seurauksia luonnonpopulaatiossa Etelä-Suomessa. Ensimmäisessä osajulkaisussa tutkin kokeellisen pesänkorkeusmanipulaation (pesän korkeus linnunpöntön sisällä) vaikutuksia poikasten kasvuun ja naaraiden somaattiseen kuntoon. Pesien koonvaihtelun on arveltu liittyvän erilaisiin pesäneristystarpeisiin, jotka johtuvat maantieteellisen sijainnin tai lämpötilan eroista. Tämän hypoteesin perusteella oletin, että kokeellisesti suurennettu pesä loisi suotuisammat olosuhteet poikasten kehitykselle ja/ tai edellyttäisi vähemmän naaraan läsnäoloa pesässä. Sinitiaisten poikaset ovat vaihtolämpöisiä ensimmäisen elinviikkonsa ajan, jolloin niiden kehonlämmön ylläpitäminen edellyttää vanhemman, yleensä naaraan, läsnäoloa. Koe vaikutti ainoastaan poikasten pyrstösulkien pituuteen, millä ei oletettavasti ole merkittävää vaikutusta yksilön kelpoisuuteen, sillä pyrstön pituuden tehtävä on lennon hienosäätö. Tulokseni eivät olennaisesti tukeneet hypoteesiä, jonka mukaan suurempi pesä olisi eristysominaisuuksiltaan pientä parempi. Muiden tutkimusten mukaan pesän pintakerroksen paksuus ja materiaalit vaikuttavat enemmän pesän eristysominaisuuksiin kuin pesän korkeus, josta suurin osa koostuu sammaleisesta pohjakerroksesta, jolla on lähinnä rakenteellinen tehtävä. Osajulkaisuissa II-IV tutkin pesänrakennuksen vaihtelun evolutiivista potentiaalia. Osajulkaisussa II käsittelin kvantitatiivisen genetiikan keinoin pesän kokoa ja materiaalisisältöä mahdollisina yksilöllisinä piirteinä tutkimalla näiden ominaisuuksien yksilöiden välistä toistuvuutta (repeatability) ja periytyvyyttä. Koska toistuvuus määrittää periytyvyyden ylärajan, siitä on perusteltua aloittaa tutkittaessa piirteen tai käyttäytymisen periytyvyyttä. Havaitsin, että sekä pesän koko että höyhenten osuus pesämateriaaleista olivat toistuvia (eli yksilöllisiä) piirteitä sinitiaisnaarailla. Lisätutkimuksen myötä selvitin, että höyhenten osuus pesästä on lisäksi lievästi periytyvä naaraisiin rajoittunut piirre. Kolmannessa osajulkaisussa tutkin sinitiaisten pesänkoristelua sekä yksilöllisten pesänpiirteiden välisiä keskinäisiä korrelaatioita. Keskityin tässä osajulkaisussa pesäkoristeisiin, jotka ovat pesän päälle aseteltuja näyttäviä sulkia ja höyheniä, mutta koristeet voivat olla myös muuta materiaalia, kuten kukkien terälehtiä, keinotekoista materiaalia, värikästä muovia tai muuta harvoin tavattua pesämateriaalia. Havaitsin, että pesänkoristelu on toistuva piirre sinitiaisnaarailla, mikä on ristiriidassa aiemmin julkaistujen tutkimusten kanssa, joiden mukaan sinitiaiskoiraat koristelevat pesän sulilla. Lisäksi havaitsin, että pesänkoristelu ja pesän höyhenten osuus korreloivat keskenään ja muodostivat yhdessä käyttäytymissyndrooman, jota kutsuimme tässä yhteydessä laajennetuksi fenotyyppisyndroomaksi. Käyttäytymissyndrooman tutkiminen edellyttää suoria havaintoja yksilöiden käyttäytymisestä. Korvasimme suorat havainnot pesänrakennuskäyttäytymisestä tutkimalla sen jäänteitä, eli pesien piirteitä. Havaittu pesänrakennussyndrooma (eli keskenään korreloivat pesänpiirteet) vihjaa, että sinitiaisten vaste pesimisympäristön muutokseen voi olla rajallinen, ainakin jos pesänpiirteet korreloivat fenotyypin lisäksi myös geneettisellä tasolla. Osajulkaisussa IV tutkin valintaa sinitiaisten pesänrakennuskäyttäytymisessä. Selvitin, onko pesänpiirteillä yhteyksiä kelpoisuuteen tutkimalla naaraan lisääntymismenestystä. Havaitsin, että vaikka pesänpiirteet eivät vaikuttaneet pesäpoikasten todennäköisyyteen selviytyä, höyhenten osuus pesässä lisäsi merkitsevästi poikasten rekrytointitodennäköisyyttä lisääntymispopulaatioon. Tämä on merkittävä löytö, sillä yhdistettynä muihin tuloksiimme (II), se on ensimmäinen todiste valinnan vaikutuksesta lintujen pesänrakennuskäyttäytymiseen. Kokeelliset tutkimukset ovat tarpeen selvittämään pesähöyhenten aiheuttama suotuisa vaikutus, josta on hyötyä vasta sen jälkeen, kun poikaset lähtevät pesästä. Väitöskirjassani tutkin sinitiaisten pesien vaihtelun syitä ja seurauksia. Kokeellisen tutkimuksen avulla havaitsin, että pesän korkeudella on vähäinen vaikutus pesän lämmönsäätelyominaisuuksiin (I). Havaitsin, että pesänkoristelu, pesän korkeus sekä höyhenten osuus pesästä ovat toistuvia piirteitä naarailla (II, III), ja löysin kvantitatiivisen genetiikan keinoin todisteita pesänrakennuskäyttäytymisen periytyvyydestä (II). Lisäksi havaitsin, että höyhenten osuus pesässä on naaraan piirre, jolla on periytyvyyden lisäksi vaikutuksia tämän kelpoisuuteen, mikä tarkoittaa, että se on valinnan kohteena (IV).